Prevalence and factors associated with unintended pregnancies in teenagers and young women in eight Sub-Saharan African countries: evidence from Performance Monitoring and Accountability cross-sectional surveys, (2017-2018) - Dobo Onivogui; Abou Coulibaly; Desire Lucien Dahourou; Seni Kouanda (Journal of Interventional Epidemiology and Public Health)
Introduction: Sub-Saharan Africa is one of the world's regions with a low modern contraceptive prevalence rate and a high prevalence of unintended pregnancies. This study aimed to explore the prevalence and contributing factors to unintended pregnancies among teenagers and young women in eight sub-Saharan African countries. Methods: We analyzed Performance Monitoring and Accountability 2020 (PMA 2020) data from eight countries in sub-Saharan Africa (Ghana, Burkina Faso, Niger, Côte d'Ivoire, Nigeria, Uganda, Ethiopia, and Kenya) that had conducted the national surveys in 2017-2018. A total of 4,914 young women aged 15 to 24 years who were pregnant at the time of data collection or who had given birth between 2016 and 2018 were involved in this study. We determined the pooled prevalence, and by country, of unintended pregnancies. We used binary logistic regression to explore the factors associated with unintended pregnancies. Results: The pooled prevalence of unintended pregnancies for all eight countries was 33.4% (95% CI =31.0 - 36.0), ranging from 13.0% (6.8 -15.1) in Niger to 55.8% (46.9 - 64.8) in Ghana. Educated women, never-married women, and women who had unmet needs for contraception were more likely to have unintended pregnancies. In contrast, women with moderately rich, rich, and very rich profiles are less likely to have unintended pregnancies. Conclusion: Despite the efforts made, the prevalence of unintended pregnancies is still high in seven countries, except Niger. Reducing unmet needs remains the priority for the prevention of unintended pregnancies